Models of BRICs' Economic Development and Challenges for EU Competitiveness - Jayati Ghosh; Peter Havlik; Marcos Poplawski-Ribeiro; Waltraut Urban (The Vienna Institute for International Economic Studies (wiiw), 2009)
The term BRICs puts under a common label the four largest fast growing emerging countries Brazil, Russia, India and China. The BRICs show many common features, such as big land size, large population, fast economic growth etc., but important differences as well, due to their different models of economic development and resources endowments. In this report, we discuss the different models of economic development of the individual BRIC countries, with a special focus on their external relations (trade, FDI) and on likely future developments. Brazil is a domestically oriented service economy; Russia's economic development is heavily dependent on energy and raw material resources; the Indian economy is essentially service-led, supported by exports; and China's economic development is driven by manufacturing exports and investment. Finally, we explore the resulting future challenges and opportunities for EU competitiveness.
Keywords: G01; O21; O53; O54; O57; 330; economic development; Brazil; Russia; India; China; the European Union; competitiveness